2017
DOI: 10.1080/10872981.2017.1392824
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, perceptions, and consequences of substance use in medical students

Abstract: Background: Research regarding the health and wellness of medical students has led to ongoing concerns regarding patterns of alcohol and drug use that take place during medical education. Such research, however, is typically limited to single-institution studies or has been conducted over 25 years ago. Objective: The objective of the investigation was to assess the prevalence and consequences of medical student alcohol and drug use and students’ perceptions of their medical school’s substance-use policies. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
98
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 25 publications
9
98
3
3
Order By: Relevance
“…He interpreted this as being positive because the students were not using drugs as a coping strategy. In contrast to other studies, which report about 30% of risky drinking habits [37] and alcohol abuse or dependence [38] among medical students, our data showed that even if the 3-month prevalence of alcohol consumption is over 90%, high-risk drinking was not very common. Overall, under 1.5% of our participants met the criteria for high-risk drinking.…”
Section: Substancecontrasting
confidence: 99%
“…He interpreted this as being positive because the students were not using drugs as a coping strategy. In contrast to other studies, which report about 30% of risky drinking habits [37] and alcohol abuse or dependence [38] among medical students, our data showed that even if the 3-month prevalence of alcohol consumption is over 90%, high-risk drinking was not very common. Overall, under 1.5% of our participants met the criteria for high-risk drinking.…”
Section: Substancecontrasting
confidence: 99%
“…Epidemiological surveys in the USA and other Western countries have documented that students enrolled in postsecondary institutions display a high prevalence of problematic use of alcohol, tobacco, and cannabis . The abuse of these substances results in enduring and severe consequences, including neurocognitive problems, poor academic performance, financial and legal repercussions, health concerns, as well as unintentional injuries and mortality . Better interventional strategies are needed for the prevention of substance use in this population, but these efforts are severely hampered by our inadequate understanding of the etiology of substance use vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The abuse of these substances results in enduring and severe consequences, including neurocognitive problems, poor academic performance, financial and legal repercussions, health concerns, as well as unintentional injuries and mortality. [9][10][11][12][13][14] Better interventional strategies are needed for the prevention of substance use in this population, but these efforts are severely hampered by our inadequate understanding of the etiology of substance use vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…Other mental health issues have been found to affect medical students. Studies in several countries have found relatively high levels of substance abuse (both alcohol and drugs) and both eating and sleep disorders [8][9][10]. The focus of this paper is on the symptoms of depression and anxiety experienced by medical students.…”
Section: Introductionmentioning
confidence: 99%